Evaluation of the presence of Adenocephalus pacificus in fish of greater consumption in Peru in the period 2016-2017 - Londoñe-Bailón, Pablo (2020)
The aim of this study was to evaluate the prevalence, abundance and average intensity of plerocercoids (PLs) of Adenocephalus pacificus in the most important commercial fish species from the Peruvian coast. A total of 28 species of fish were sampled and 12 017 specimens were analysed. The presence of PLs of A. pacificus were determined from Peruvian anchovy (Engraulis ringens), lorna drum (Sciaena deliciosa), striped mullet (Mugil cephalus), horse mackerel (Scomber japonicus), Peruvian rock sea bass (Paralabrax humeralis) and cabinza grunt (Isacia conceptionis) with a prevalence of 0.55, 24.96, 0.56, 1.79, 1.53 y 3.94%, respectively. Three different types of scolex of A. pacificus PLs, like as spherical, lanceolate, heart-shaped were identified, regardless of the host, area and sampling period.